The Relationship Between Corporate Philanthropy And Shareholder Wealth: A Risk Management Perspective - Godfrey, Paul C. (Academy of Management Review, 2005)
I present a complex theoretical explanation that draws on multiple bodies of literature to present an academically rigorous version of a simple argument: good deeds earn chits. I advance/defend three core assertions: (1) corporate philanthropy can generate positive moral capital among communities and stakeholders, (2) moral capital can provide shareholders with insurance-like protection for a firm's relationship-based intangible assets, and (3) this protection contributes to shareholder wealth. I highlight several managerial implications of these core assertions.